THE INFLUENCE OF PRINCIPAL’S LEADERSHIP STYLE, TEACHER’S COMMITMENT AND WORK SPIRIT ON TEACHER’S PERFORMANCE IN JUNIOR HIGH SCHOOL IN BANJARBARU CITY - Juaini; Aslamiah; Suhaimi (Journal of K6, Education and Management, 2019)
This study aims to describe the influence of the principal's leadership style, teacher's work commitment, teacher's work spirit, towards the teacher?s performance of junior high school teachers in Banjarbaru City. The sample is determined through the steps of determining the proportional random sampling technique of each member of the sub-population based on the number of schools studied so that a sample of teachers is obtained to study 225 people. The results showed: There was a significant direct effect on the principal's leadership style, the work commitment of teachers to the work spirit of junior high school teachers in Banjarbaru City. There is a significant direct effect of teacher morale, school principal leadership style, and teacher work commitment on the performance and there is a significant indirect effect of the principal's leadership style and teacher's work commitment through the teacher's work enthusiasm on the performance. The result it is expected that they can understand the types of good leadership, and then can be applied in the school environment to provide examples and support for teachers to have a high spirit or work and work commitment in achieving better performance.